Seroprevalence of Dengue Among Healthcare Workers: Assessing Infection Risk and Preventive Strategies in a Tertiary Care Hospital. - Abid, Seemab; Umar, Muhammad; Ambreen, Saima; Mujeeb Khan; Iqbal, Mehwish; Jabeen, Kehkshan; Nadeem, Misbah (International Journal of Endorsing Health Science Research, 2025)
Background: Dengue fever is a significant public health concern, particularly in endemic regions like Pakistan. Healthcare workers (HCWs) are at an increased risk of infection during outbreaks due to their close proximity to infected patients. Effective vector control and preventive measures are crucial in minimizing disease transmission in healthcare settings. This study aimed to assess the seroprevalence of dengue among healthcare personnel and evaluate the effectiveness of preventive strategies implemented in a tertiary care hospital. Methodology: A cross-sectional study was conducted among 110 healthcare workers, including house officers, postgraduate trainees, consultants, nurses, ward attendants, and sanitary staff from the Department of Infectious Diseases at Holy Family Hospital. Blood samples were tested for the presence of the NS1 antigen, IgM, and IgG antibodies. Statistical analyses, including chi-square tests, were performed to determine associations between serological results and sociodemographic factors. Results: The study population was predominantly female (66.4%), with nurses constituting the largest professional group (59.1%). All participants tested negative for NS1 antigen and IgM antibodies, indicating no active dengue infections. However, 3.6% tested positive for IgG antibodies, suggesting past dengue exposure. There was no statistically significant association between IgG positivity and gender (p = 0.480) or professional category (p = 0.336). Conclusion: The low seroprevalence of dengue among healthcare workers in this study suggests that effective vector control and preventive measures may have contributed to minimizing infection risk. Strengthening hospital-based mosquito control strategies and ongoing education for healthcare personnel remain essential to further reducing dengue transmission in clinical settings.